STRATEGI PEMBELAJARAN JOYFULL LEARNING PADA MATA PELAJARAN FIQIH DI MTs NEGERI 3 DONGGALA - Siti Nuroh; Khairul Khatami; M. Sulhan (Journal of Public Policy Analys, 2023)
Research on "Joyful Learning Learning Strategies in Fiqh Subjects at MTs Negeri 3 Donggala" is focused on the implementation of Joyful learning learning strategies, opportunities and challenges in learning on Fiqh subjects. Research based on field research, with the presentation of qualitative descriptive data. Data collection techniques through observation, interviews and documentation were then reduced, presented and verified. The research findings describe that in the joyfull learning strategy, a teacher in the learning process uses a fun strategy, collaborating learning with stories and jokes, accompanied by the delivery of learning material using a variety of methods that support the creation of a relaxed, light and fun learning atmosphere.